Retrospective analysis of wall waterproofing structures to determine the main directions of the relevant restoration work - Semko, Oleksandr; Filonenko, Olena; Yurin, Oleg; Mahas, Mahas; Rudenko, Viktor; Ilchenko, Tetiana (Academic journal Industrial Machine Building Civil Engineering, 2023)
The rationality of the constructive solution of foundations and plinths of buildings depends on the amount of moisture in the soil. It is influenced by the level of groundwater, atmospheric precipitation, the quality of the vertical planning of the area around the building, the quality of construction work when forming a paving in the near-wall part of the building and the presence of hard coatings in the improvement of the area around the building. In order to determine rational structural solutions that prevent the building plinths from getting wet, a retrospective analysis of the design options for building plinths in different time periods was carried out. The period from the middle of the 19th century to the present is considered, because during this period a number of changes occurred related to socio-economic transformations in society and significant scientific and technological progress. As a result of a retrospective analysis of waterproofing structures at the foundation parts of the walls, it was found that until 1953 in domestic construction practice there was no mandatory requirement for such waterproofing due to the lack of mass production of appropriate materials. Since 1956, with the transition of construction practices to an industrial basis, they have been developed as typical options for waterproofing walls using mass-produced materials. In modern conditions of construction practice, especially in such areas as reconstruction and restoration, it is necessary to use an individual approach to solve local problems of waterproofing the walls of buildings.
Keywords: waterproofing; foundation; plinth; historical buildings